PERLINDUNGAN HUKUM HUMANITER INTERNASIONAL TERHADAP WARTAWAN DALAM KONFLIK BERSENJATA - Polii, Miracle Sangkoy; Lombok, Lesza Leonardo; Lumenta, Henry Noch (Jurnal Yustitia, 2025)
This study examines the protection of international humanitarian law for journalists working in armed conflict situations. Journalists, as key actors in providing information to the global public, often face serious dangers when covering armed conflicts. This raises questions about the effectiveness of existing international legal protections for them. This research employs a normative legal approach by reviewing international regulations such as the 1977 Additional Protocol I to the Geneva Conventions and Article 4A(4) of the 1949 Geneva Convention III, which provide protection for journalists in war zones. Although international humanitarian law regulates the protection of journalists, field practices show that violations of journalists’ rights still frequently occur. Based on these findings, this study recommends strengthening the implementation of international humanitarian law and increasing global awareness of the importance of protecting journalists in conflict areas. The results of this research are expected to contribute theoretically to the development of humanitarian law and provide practical benefits for journalists carrying out their duties in armed conflict zones.